Exercise-induced bronchoconstriction in university field hockey athletes: Prevalence, sex differences, and associations with dyspnea symptoms - Needham, Robert S.; Sharpe, Graham R.; Williams, Neil C.; Lester, Paul A.; Johnson, Michael A. (Frontiers in Allergy, 2022)
Introduction Exercise-induced bronchoconstriction (EIB) is a prevalent condition in athletes. EIB screening studies identify many athletes with undiagnosed EIB. Moreover, there is a poor relationship between EIB and dyspnea symptoms recalled from memory. Purpose This study investigated: (I) the prevalence of EIB in British university field hockey athletes; (II) the effect of sex and diagnostic criteria on EIB prevalence; and (III) the association between EIB and contemporaneous dyspnea symptoms. Methods 52 field hockey athletes (age: 20 ± 2 years; height: 173 ± 9 cm; body mass: 72 ± 10 kg; male = 31; female = 22) completed a eucapnic voluntary hyperpnea (EVH) test with multi-dimensional dyspnea scores measured 3-10 minutes post-EVH. A test was deemed positive (EIB+) if a fall index (FI) ≥10% in FEV1 occurred at two consecutive time points post-test (FIATS). Two further criteria were used to assess the effect of diagnostic criteria on prevalence: FI10%, determined by a pre-to-post-EVH fall in FEV1 of ≥10% at any single time-point; and FI≥10%-NORM calculated as FI10% but with the fall in FEV1 normalized to the mean ventilation achieved during EVH. Results EIB prevalence was 19% and greater in males (30%) than females (5%). In EIB+ athletes, 66% did not have a previous diagnosis of EIB or asthma and were untreated. Prevalence was significantly influenced by diagnostic criteria (P = 0.002) ranging from 19% (FIATS) to 38% (FI≥10%-NORM). Dyspnea symptoms were higher in EIB+ athletes (P ≤ 0.031), produced significant area under the curve for receive operator characteristics (AUC ≥ 0.778, P ≤ 0.011) and had high negative prediction values (≥ 96%). Conclusion Overall, 19% of university field hockey athletes had EIB, and most were previously undiagnosed and untreated. EVH test diagnostic criteria significantly influences prevalence rates, thus future studies should adopt the ATS criteria (FIATS). Contemporaneous dyspnea symptoms were associated with bronchoconstriction and had high negative prediction values. Therefore, contemporaneous dyspnea scores may provide a useful tool in excluding a diagnosis of EIB.